ANALYSIS OF A POSSIBILITY TO CANCEL FLIGHT TIME BOUNDARIES IN PILOT TRAINING IN CONJUNCTION WITH COMPETENCE BASED TRAINING IMPLEMENTATION - Pitor, Ján; Havel, Karel (Doprava a spoje, 2012)
This paper provides outcomes of an analysis of a possibility to cancel flight time boundaries in pilot training, such as minimum or maximum flight time, in conjunction with competence based training implementation. This analysis was conducted using methods of mathematical statistics on a data set acquired at the Flight training organisation of the University of Žilina.